2021
DOI: 10.1108/ilt-08-2020-0310
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of dimple structure on aluminium silicon alloy fabricated using turning machine

Abstract: Purpose This research aims to present the characteristics of dimple structure which was fabricated using a turning machine, where the characteristics include sizes, shapes, area ratio and aspect ratio. This research aims at filling the gap in the machining parameters of previous research in producing dimple by using turning process with the aid of dynamic assisted tooling for turning (DATT). In producing dimple, a carbide insert grade H1 was used on a hypereutectic aluminium silicon alloy (A390) material. Dimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Larger clearance is presented at the higher-pressure side, while smaller clearance faces the lower pressure side, causing impedance in the flow, thus enhancing the load-carrying capacity. Recent study by Nasir et al 49 showed various shapes and sizes of ellipse dimples dimple that can reduce the friction were fabricated using turning process which is environmentally friendly and suitable for mass production.…”
Section: Resultsmentioning
confidence: 99%
“…Larger clearance is presented at the higher-pressure side, while smaller clearance faces the lower pressure side, causing impedance in the flow, thus enhancing the load-carrying capacity. Recent study by Nasir et al 49 showed various shapes and sizes of ellipse dimples dimple that can reduce the friction were fabricated using turning process which is environmentally friendly and suitable for mass production.…”
Section: Resultsmentioning
confidence: 99%